Educational Norms and Values in the Tradition of Dumia um Banua in North Minahasa - Mayske Rinny Liando; Grace Shirley Luntungan; Gerry Kadamehang; Viktory Nicodemus Joufree Rotty; Chika Dwi Putri Ansik (STAI Hubbulwathan Duri, 2022)
Tradition is part of people's lives, because various activities are carried out according to traditions that have been passed from generation to generation. Likewise with the Dumia um Banua tradition which is an ancestral cultural heritage that has an important role in people's lives in Laikit Village. This study aims to describe the Dumia um Banua process, as well as the educational norms and values contained in the Dumia um Banua tradition in Laikit Village, Dimembe District, North Minahasa Regency. The method used is descriptive qualitative method. The results showed that the Dumia um Banua tradition took the form of a traditional ceremony as a form of thanksgiving and entertainment that contained religious, moral, and social educational values. Cultural assets that must be preserved and maintained.